Treatment of Naoxueshu Promotes Improvement of Hematoma Absorption and Neurological Function in Acute Intracerebral Hemorrhage Patients - Song, Juexian; Lyu, Yi; Wang, Pingping; Nie, Yuting; Lu, Huiqiang; Gao, Li; Tong, Xiaolin (Frontiers in Physiology, 2018)
Aims: To evaluate the clinical efficacy of Naoxueshu oral liquid in the treatment of intracerebral hemorrhage (ICH) patients. Methods: In our study, December 2008 to August 2010, 88 patients with intracerebral hemorrhage were enrolled and 87 patients with complete information of whom 44 patients received Naoxueshu oral liquid plus regular treatment (Naoxueshu group), 43 patients received regular treatment (control group) only. Naoxueshu oral liquid 10ml was taken in the Naoxueshu group, with 3 times a day for 21 consecutive days. The regular treatment included (1) dehydration treatment by 20% mannitol; (2) therapy to deal with complications including; (3) supportive therapy. The general clinical information, neurological assessment information, laboratory information, and the hematoma volume information were collected and analyzed pre-and post-treatment. Results: We did not find differences in the information between two groups before treatment (p>0.05). 21-day after treatment, the white blood cell (WBC) count, hematoma volume, the National Institutes of Health Stroke Scale (NIHSS) score, modified Rankin Scale ( mRS), Barthel index (BI) and traditional Chinese medicine (TCM) syndrome score in the Naoxueshu group and control group were significantly decreased than before (pnaoxueshu<0.01, pcontrol<0.05), and the changes of the WBC count, hematoma volume, NIHSS score, mRS score and TCM syndrome score in Naoxueshu group were greater than that of control group (P<0.001). Conclusion: Naoxueshu oral liquid plus regular treatment could decrease the inflammatory response and hematoma, and improve outcomes of ICH patients than regular treatment only. This suggests that Maixueshu oral liquid is a potential treatment for ICH patients.